HGG-22. EVALUATING THE REGULATION OF BLOOD-BRAIN BARRIER INTEGRITY IN DIPG MOUSE MODELS. (1st June 2021) - Wei, Xin; Phoenix, Timothy
Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are considered to maintain a fairly intact blood-brain barrier (BBB) based on patient imaging tumor histology. In characterizing recently developed DIPG and HGG mouse models, we identified differences in BBB function and increased Angiopoietin1 (Angpt1) in H3 K27M DIPG models. We hypothesize that H3 K27M mutations promote the maintenance of DIPG BBB integrity through upregulation of Angpt1. To determine DIPG and HGG BBB phenotypes we performed an intergrative analysis of vascular histology and endothelial transcriptomes Ongoing studies using electroporation based DIPG mouse models are being performed examine the regulation and function of Angpt1 in DIPG BBB integrity. We have initiated studies comparing H3 K27M DIPG mouse models to H3 WT and G34R cortical HGG mouse models, demonstrating that DIPG models show minimal changes in vascular phenotype, including vessel density, branching, and diameter compared to cortical HGG models. Comparing DIPG and HGG purified endothelial transcriptomes, HGG ECs displayed enrichments of inflammatory signals and proliferation gene sets, and increased expression of tip cell identity genes. We identified Angpt1 as selectively upregulated in H3 K27M mouse models and derived cell lines. Preliminary data suggests Angpt1 supports the maintenance of BBB integrity in DIPG models. BBB phenotype differences are present in DIPG and HGG mouse models. Uncovering mutation specific mechanisms that regulate BBB function in brain tumors will be critical to advance our understanding of brain tumor pathogenesis and treatment response.